Učitelji o jezikovnih vprašanjih pri vključevanju učencev priseljencev v slovenski vzgojno-izobraževalni sistem - Budinoska, Ines (Jezik in slovstvo, 2017)
The paper presents the findings of research conducted within my doctoral studies, which are also part of my doctoral dissertation (entitled: Linguistic integration of immigrants' children in Slovenian basic school, 2014). One of the previous issues (58/2) presented the results regarding teachers' strategies for the inclusion of immigrant pupils in classes, while the present paper focuses on the part of research dedicated to the positions of teachers on language issues related to the inclusion of immigrant children in the Slovenian education system. This part of the research was thus focused on teachers' attitudes towards the use of different languages during the inclusion of immigrant children in classes, and on the use, learning and teaching of the immigrant children's mother tongue
Keywords: učenci priseljenci; jezikovna integracija; večjezičnost; izobraževalni sistem; Slovenia; Slovenija